1989
DOI: 10.1177/0013916589211002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Setting on Window Preferences and Factors Associated with Those Preferences

Abstract: Window preference research on a few settings has found that windows are generally preferred and that larger windows are preferred over smaller ones. No theoretical model of window preferences, however, has been proposed. The present experiment was designed to investigate window preferences across a large variety of common spaces and to examine reasons orfactors that may underlie these preferences with the ultimate goal of predicting them. Window preferences, in terms of size, number, and degree of transparency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 9 publications
3
43
0
Order By: Relevance
“…Nasar (1983) claims that ' people preferred residential scenes which were described as ornate, well kept, open and clear in use ' (p. 589). Butler and Biner (1989) argue that the generalization of the notion that people prefer large windows over small, medium or no windows is not true. Crosscultural studies comparing people of different backgrounds have expanded the knowledge about their possible similarities and differences ( Nasar, 1984 ) Amole (2005) who studied residence hall of 20 universities in southwest Nigeria found that ' one of the attributes of the bedroom that contributed negatively to satisfaction with the bedroom was privacy ' .…”
Section: Literature Reviewmentioning
confidence: 93%
“…Nasar (1983) claims that ' people preferred residential scenes which were described as ornate, well kept, open and clear in use ' (p. 589). Butler and Biner (1989) argue that the generalization of the notion that people prefer large windows over small, medium or no windows is not true. Crosscultural studies comparing people of different backgrounds have expanded the knowledge about their possible similarities and differences ( Nasar, 1984 ) Amole (2005) who studied residence hall of 20 universities in southwest Nigeria found that ' one of the attributes of the bedroom that contributed negatively to satisfaction with the bedroom was privacy ' .…”
Section: Literature Reviewmentioning
confidence: 93%
“…Butler and Biner [15] found in their survey conducted in Indiana, USA, that the preference for windows and their size varied according to the type of space. Contrary to previous research which showed a general preference for large windows, this study provided evidence that large windows were not the preferred choice for the majority of spaces.…”
Section: Preferred Window Typementioning
confidence: 99%
“…In a windowless offi ce, people often decorate the space with posters of outdoor scenes ( Heerwagaen and Orians, 1986 ), but in a computer room, people tend to cover up existing windows ( Butler and Binder, 1989 ). Tabet-Aoul believes that occupants ' attitudes towards window preferences are infl uenced by previous experiences, which means that the differences in social and cultural factors lead to different expectations and responses (2001).…”
Section: Human -Window Interactions Studiesmentioning
confidence: 99%
“…The natural daylight and ventilation provision was replaced by the prescriptive standard of artifi cial lighting and mechanical ventilation, where performance is supposed to be equivalent to the natural provision. Some studies in Western countries proved that there may be some often-used spaces for which people do not have a strong desire for windows, especially considering privacy ( Butler and Binder, 1989 ). Residents in Hong Kong think the psychological benefi ts of windows cannot be substituted, while when windows are provided, people are more concerned about physical environment, such as ventilation and daylighting.…”
Section: Hygiene Conditions For Toiletsmentioning
confidence: 99%